Kinerja Pegawai di Kantor Camat Rumbai Pekanbaru - Pamungkas, Dimas Danu; Saputri, Selvi Maharani; Rahmadhani, Ririn; Nielwaty, Elly (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
The analysis of employee performance at the Rumbai Sub-district Office, Pekanbaru City, aims to evaluate the effectiveness and efficiency of public services provided by employees. This study uses a descriptive method with a qualitative approach, involving interviews and direct observation of employees and the community. The results of the analysis show that employees at the Rumbai Sub-district Office have a high commitment to their duties, supported by good teamwork and innovation in service. In addition, training and development provided to employees contribute positively to improving performance. Transparent performance assessment is also an important factor in encouraging employees to achieve the set targets. Overall, employee performance at the Rumbai Sub-district Office is very good, which has a positive impact on community satisfaction and the achievement of regional development goals.